Oxford Research Encyclopedia of Politics 2021
DOI: 10.1093/acrefore/9780190228637.013.1610
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Responsive Crisis Management: Institutional Design and Information

Abstract: The requirements for effective and responsive crisis management have developed significantly in the face of proliferating transboundary crises and rising societal demands during the information revolution. As crises disturb more and more societal strata and rapidly span across different types of networks, traditional crisis structures need to become more open and responsive. To deal with these contemporary requirements of crisis management, renewed institutional designs are needed. Institutional designs reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Three modes of governance are distinguished in this body of literature: Participant-governance, lead-organization governance, and governance by a network administrative organization (Provan & Kenis, 2008). These modes of governance can be related to governance embedded in the Incident Command System (ICS) (Boersma & Wolbers, 2021;Moynihan, 2009). ICS is a widely used modular emergency management command structure, originally designed to combat wildland fires in California in the early 1970s (Bigley & Roberts, 2001).…”
Section: Network Approaches In Crisis Management and Disaster Studiesmentioning
confidence: 99%
“…Three modes of governance are distinguished in this body of literature: Participant-governance, lead-organization governance, and governance by a network administrative organization (Provan & Kenis, 2008). These modes of governance can be related to governance embedded in the Incident Command System (ICS) (Boersma & Wolbers, 2021;Moynihan, 2009). ICS is a widely used modular emergency management command structure, originally designed to combat wildland fires in California in the early 1970s (Bigley & Roberts, 2001).…”
Section: Network Approaches In Crisis Management and Disaster Studiesmentioning
confidence: 99%
“…Some studies have found that managers do not invest resources in crisis prevention because they believe that the crisis will, in most cases, unfold differently than their expectations [6,7]. Other managers believe that there is no need to make such response plans [8] because their organisation is strong enough to overcome any risk and has the right strategic partner, the perfect product, or sufficient financial backing [9,10]. A crisis resulting from dynamic changes in the external environment has the potential to threaten the sustainability and put the survival of the company at risk [11] if adequate action is not taken to overcome it [12].…”
Section: Introductionmentioning
confidence: 99%